Dampak TikTok Terhadap Perubahan Perilaku Sosial dan Nilai Kultural Generasi Z - Syahri, Firdania Maulida; Nabila, Nabila; Maharani, Nisa Aulia; Ridho , Kholis (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
TikTok is changing generation Z's interactions, communications, and identity formation, influencing social behavior and cultural values ​​with both positive and negative impacts. (1) The development of digital technology has changed the way generation Z interacts, which is very dependent on social media such as TikTok. This application has become a global phenomenon with significant influence on social and cultural aspects. (2) This research aims to explore the impact of TikTok on changes in social behavior and cultural values ​​of generation Z, including positive and negative aspects. (3) The research used a descriptive qualitative method with a symbolic interactionism theory approach and cultivation theory, through questionnaires and structured interviews with 109 respondents. (4) TikTok makes it easier to access information and strengthens social values ​​such as empathy and diversity, but it also influences social interaction patterns and creates social pressure for users. This platform also changes the way we view local culture, with a tendency to adopt global trends. Conclusion: TikTok plays a role in shaping the social behavior and cultural values ​​of generation Z, but a balance is needed between freedom of expression and preserving local values ​​to mitigate its negative impact in the digital era.